(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study investigates the hepatoprotective potential of Monotheca buxifolia fruit hydro-ethanolic extract, against isoniazid- and rifampicin- induced hepatotoxicity in rats. Phytochemical investigations lead to the isolation of oleanolic acid and isoquercetin. Pretreatment with M. buxifolia extract at doses of 150 and 300 mg/kg for 21 days, restored the isoniazid- and rifampicin-induced elevation of serum levels of alanine aminotransferase (p<0.001), aspartate aminotransferase (p<0.001 and p<0.05), alkaline phosphatase (p<0.001), billirubin (p<0.001) and total proteins (p<0.001) as well as afforded significant protection against histopathological changes in the liver. From these results, it is conceivable that M. buxifolia exhibited selective protective effect against isoniazid- and rifampicin-induced hepatotoxicity, mediated through the presence of oleanolic acid and isoquercetin. Video Clip of Methodology: 51 sec: Full screen Alternate 54 sec: Full Screen Alternate